AFTA and the intra-trade patterns among ASEAN-5 economies: trade-enhancing or trade-inhibiting? - Siah, Kim Lan; Choong, Chee Keong; Yusop, Zulkornain (Canadian Center of Science and Education, 2009)
This paper examines ASEAN economic integration and its ability to promote intra-ASEAN trade, namely, Indonesia, Malaysia, Philippines, Singapore and Thailand. In order to achieve this goal, a modified gravity model is estimated within autoregressive distributed lag (ARDL) framework, or bounds testing approach for each of the five ASEAN countries based on data from year 1970 to year 2001. The empirical results indicate that the effects of the size of economy on bilateral trade flow in ASEAN are either trade-enhancing or trade-inhibiting dependent on the country-specific. There is evidence that AFTA preferential arrangements are important and prevalent in enhancing intra-ASEAN trade. However, ASEAN countries may not as a whole benefit from the formation of AFTA as the trade deflection might occur in the regional market.